AB0022 Influence of mhciita RS3087456 and RS4774 polymorphisms in the susceptibility to cardiovascular disease of patients with rheumatoid arthritis. (23rd January 2014) - García-Bermúdez, M.; González-Juanatey, C.; Lόpez-Mejías, R.; Blanco, R.; Rodriguez-Rodriguez, L.; Pérez-Esteban, S.; Castañeda, S.; Urcelay, E.; Miranda-Filloy, J.A.; Gόmez-Vaquero, C.; Fernández-Gutiérrez, B.; Balsa, A.; et al.
Abstract : Background: Rheumatoid arthritis (RA), a chronic autoimmune disease, is associated with accelerated atherosclerosis. Results from GWAS of UK, US and European families with RA (1, 2, 3) have identified linkage to the chromosome 16p13 locus. MHCIITA is a major regulator of MHC expression that has also been reported to be involved in the susceptibility to myocardial infarction (4). Objectives: In this study we investigated the potential association of two MHCIITA gene polymorphisms with cardiovascular (CV) risk in patients with RA. Methods: 1302 patientsfulfilling the 1987 ACR classification criteria for RA were genotyped for the MHCIITA rs3087456 and rs4774 gene polymorphisms to determine the influence of MHCIITA variants in the development of CV events. The potential influence of these polymorphisms in the development of subclinical atherosclerosis was also analyzed in a subgroup of patients with no history of CV events by the assessment of two surrogate markers of atherosclerosis; brachial and carotid ultrasonography to determine endothelial function and carotid artery intima-media thickness, respectively. Results: No statistically significant differences in the allele or genotype frequencies for each individual MHCIITA gene polymorphism between RA patients who experienced CV events or not were found. It was also the case when each polymorphism was assessed according to results obtained from surrogate markers of atherosclerosis. Also, in assessing the combined influence of both MHCIITA gene polymorphisms in the risk of CV disease after adjustment for gender, age at time of disease diagnosis, follow-up time, traditional CV risk factors, and shared epitope status, patients with CV events only showed a marginally decreased frequency of the MHCIITA rs3087456-rs4774 G-G allele combination ( p =0.08; OR: 0.63 [95%CI: 0.37- 1.05]). Conclusions: Our data do not support an influence of MHCIITA rs3087456 and rs4774 polymorphisms in the increased risk of CV events of RA patients. Acknowledgments: Supported by two grants from Fondo de Investigaciones Sanitarias PI06-0024 and PS09/00748 (Spain). This work was partially supported by RETICS Program, RD08/0075 (RIER) from Instituto de Salud Carlos III (ISCIII), within the VI PN de I+D+i 2008-2011 (FEDER). MGB is a recipient of a grant from Fundaciόn Española de Reumatología (FER). References: Mackay K, Eyre S, et al. Arthritis Rheum 2002; 46:632-9. John S, Shephard N, et al. Am J Hum Genet 2004; 75:54–64. Eyre S, Barton A, et al. Arthritis Rheum 2004; 50:729–35. Swanberg M, Lidman O, et al. Nat Genet 2005; 37:486-94. Disclosure of Interest: None Declared